Legal Reform in Indonesia’s Natural Resource Exploitation: A Study of SOE Privatization and Corporate Responsibility - Suherman, Suherman; Joesoef, Iwan Erar; Bakhtiar, Handar Subhandi; Kholiq, Abdul; Phuoc, Jeong Chun (Universitas Negeri Semarang, 2025)
The purpose of this study is to examine the exploitation of natural resources by State-Owned Enterprises (SOEs), particularly in forest management and mining, which do not contribute to the prosperity of the people. The scope of this research focuses on SOEs that control vital natural resources affecting the livelihoods of many people. This research employs a normative juridical method with a historical approach to privatization and an analysis of John Ruggie’s principles regarding Government and Private Responsibility for Human Rights (“Protect, Respect and Remedies”), as well as collecting data as library research. The findings indicate that such exploitation is carried out by SOEs (with share-persero) as a result of the privatization in the 1980s and 1990s, leading to liberalization. The study of John Ruggie’s principles highlights the obligation of both the State and SOEs to prevent the exploitation of natural resources. The study concludes that the SOE engaged in resource management operate as “persero” entities, with shares partially owned by the private sector, leading to unfair business competition. Article 33 (2) and (3) of the Constitution mandates that natural resource management should be carried out by SOEs of which ownership is 100% by the State (“perum”) or through Cooperatives, as stipulated in Article 33 of the Constitution. The authors have proposed the liberalization results in the of SOEs (Persero), enabling private management, which raises concerns over monopolistic practices, unfair competition, and rationally impacts the potential of natural resources based on privatization and liberalization factors.